Правова природа відносин, що складаються в сфері емісійної діяльності держави - Царьова, Людмила Кузьмівна; Царева, Людмила Кузьминишна; Careva, Ljudmila (My University, 2012)
Article is devoted to consideration of the relations developing in the sphere of issue activity of the state as financial activity making it. Definition of issue legal relationship is made and the conclusion is given reason that they are obligations financial legal relations.
Царьова Л. К. Правова природа відносин, що складаються в сфері емісійної діяльності держави / Л. К. Царьова // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Т. 12. – С. 48-56.
Keywords: фінансова діяльність держави; емісія; гроші; емісійні зобов'язання; емісійна діяльність; емісійні правовідносини; суб'єкти емісійних правовідносин; финансовая деятельность государства; эмиссия; деньги; эмиссионная деятельность; эмиссионные правоотношения; субъекты эмиссионных правоотношений; эмиссионные обязательства; the financial activities of the state; issue; money; issue activity; issue legal relationship; subjects of issue legal relationship; issue obligations